THE EFFECT OF ESG DISCLOSURE ON ABNORMAL RETURN MODERATED BY FINANCIAL HEALTH DURING COVID-19 PANDEMIC IN INDONESIA - Maghfira, Arina; Utomo, Dwi Cahyo (Diponegoro Journal of Accounting, 2024)
This study examines the effect of ESG disclosure on abnormal return moderated by financial health during Covid-19 pandemic in Indonesia. ESG disclosure are assessed through the GRI Standard 2016 meanwhile abnormal return is calculated using the market-adjusted model. The population comprises manufacturing and energy companies listed on the Indonesia Stock Exchange (IDX) during 2020-2022. The sampling technique used in this study was a purposive sampling method with specific criteria, resulting in 104 sample companies being examined. Data analysis was performed using multiple linear regression and moderated regression analysis. The analysis results show that ESG disclosure significantly positively affects abnormal returns. In addition, financial health is shown to moderate the relationship between ESG disclosure and abnormal return, with the effect of increasing rather than decreasing the relationship.